Decrease in pain perception during acute SARS-CoV-2 infection: a case series. Issue 6 (11th June 2022) - Hentsch, Lisa; Stancu, Patrick; Allali, Gilles; Lövblad, Karl-Olof; Lobrinus, Johannes A.; Cocetta, Sara; Pautex, Sophie; Uginet, Marjolaine; Serratrice, Jacques; Coen, Matteo
Abstract : Temporary chronic pain reduction related to acute COVID-19 has been observed, providing new knowledge on the possible mechanisms of pain modulation and potential therapeutic options. Abstract: Many reports have described pain appearance or an increase of chronic pain concomitant to severe acute respiratory syndrome coronavirus 2 infection. Here, we describe the cases of 3 patients with chronic cancer pain, in which COVID-19 was associated with a dramatic reduction or disappearance of pain. Pain reappeared after recovery from COVID-19. Neurological imaging and pathological findings, when available, were inconclusive. To the best of our knowledge, this is the first case series reporting an acute reduction in pain perception in COVID-19. We believe further investigation is mandatory because it could shed new light on the mechanisms of pain perception and modulation.